2018
DOI: 10.21608/ejhm.2018.9142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraperitoneal Ketamine as Postoperative Analgesia in Laparoscopic Cholecystectomy

Abstract: Background: Laparoscopic surgery is gaining popularity so different modalities of pain management should be used as patients experience postoperative pain of different sources especially from the abdomen, back and shoulder region which is severe especially in first postoperative hours. Objective: We aimed to evaluate effect of intraperitoneal instillation of ketamine and normal saline on postoperative pain and analgesic requirements after laparoscopic cholecystectomy. Patients and Methods: Forty patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Regarding ketamine side effects, it is assumed that in sub-anesthetic doses, side effects are infrequent. In Shawky's study [32], perioperative administration of 0.5 mg/kg ketamine, given intraperitoneally, provides effective pain relief without side effects in patients undergoing laparoscopic surgery and this goes with our study that showed absence of any side effects in BK group. On the other hand, a study by Lee and his colleagues [36] have reported 44% incidence of psychomimetic side effects in patients who had received ketamine/ropivacaine in interscalene block.…”
Section: Tablesupporting
confidence: 83%
See 3 more Smart Citations
“…Regarding ketamine side effects, it is assumed that in sub-anesthetic doses, side effects are infrequent. In Shawky's study [32], perioperative administration of 0.5 mg/kg ketamine, given intraperitoneally, provides effective pain relief without side effects in patients undergoing laparoscopic surgery and this goes with our study that showed absence of any side effects in BK group. On the other hand, a study by Lee and his colleagues [36] have reported 44% incidence of psychomimetic side effects in patients who had received ketamine/ropivacaine in interscalene block.…”
Section: Tablesupporting
confidence: 83%
“…This could be attributed to the early administration of ketamine at the beginning of the operation. This differs from Shawky's results [32] who administered ketamine at the end of operation. Their patients in ketamine group were sedated for 30 min after extubation.…”
Section: Tablecontrasting
confidence: 79%
See 2 more Smart Citations
“…11,12 Ropivacaine was preferred over bupivacaine due to its improved safety profile and reduced side effects, with its vasoconstrictive properties aiding in minimizing systemic absorption and lowering the risk of cardiac and neurological complications. 8,9 The addition of adjuvants like dexmedetomidine to reduce the dosages of local anesthetics such as ropivacaine has been shown to enhance analgesic efficacy while reducing potential side effects. Studies have indicated that combining ropivacaine with dexmedetomidine resulted in prolonged pain relief and decreased total pain medication requirements compared to using fentanyl.…”
Section: Intraperitoneal Ropivacainementioning
confidence: 99%